Chromosome 17p Homodisomy Is Associated With Better Outcome in 1p19q Non-Codeleted and IDH-Mutated Gliomas. (8th July 2016) - Labussière, Marianne; Rahimian, Amithys; Giry, Marine; Boisselier, Blandine; Schmitt, Yohann; Polivka, Marc; Mokhtari, Karima; Delattre, Jean-Yves; Idbaih, Ahmed; Labreche, Karim; Alentorn, Agusti; Sanson, Marc
Abstract : Background: The 1p19q non-codeleted gliomas with IDH mutation, defined as "molecular astrocytomas, " display frequent TP53 mutations and have an intermediate prognosis. We investigated the prognostic impact of copy number-neutral loss of heterozygosity (CNLOH) in 17p in this population. Methods: We analyzed 793 gliomas (206 grade II, 377 grade III, and 210 grade IV) by single nucleotide polymorphism array and for TP53 mutations. Results: Homodisomy revealed by CNLOH was observed in 156 cases (19.7%). It was more frequent in astrocytomas and oligoastrocytomas (98/256, 38%) than oligodendrogliomas (28/327, 8.6%; p < .0001) or glioblastoma multiforme (30/210, 14.3%; p < .0001), tightly associated with TP53 mutation (69/71 vs. 20/79; p = 2 × 10 −16 ), and mutually exclusive with 1p19q codeletion (1/156 vs. 249/556; p < .0001). In the group of IDH -mutated 1p19q non-codeleted gliomas, CNLOH 17p was associated with longer survival (86.3 vs. 46.2 months; p = .004), particularly in grade III gliomas (overall survival >100 vs. 37.9 months; p = .007). These data were confirmed in an independent dataset from the Cancer Genome Atlas. Conclusion: CNLOH 17p is a prognostic marker and further refines the molecular classification of gliomas. Abstract : Seven hundred ninety-three gliomas (grades II–IV) were analyzed by single nucleotide polymorphism array and for TP53 mutations. Homodisomy revealed by copy number-neutral loss of heterozygosity (CNLOH) was observed in 156 cases (19.7%), was tightly associated with TP53 mutation, and was mutually exclusive with 1p19q codeletion. In IDH -mutated 1p19q non-codeleted gliomas, CNLOH 17p was associated with longer survival (86.3 vs. 46.2 months), particularly in grade III gliomas (>100 vs. 37.9 months).